Pemeriksaan Kesehatan Gratis di Posyandu Bindu Anggrek Kota Cimahi: Pengabdian - Edah Jubaedah; Anna Christina Ikasari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Routine health check-ups play a crucial role in early detection and prevention of non-communicable diseases such as diabetes, hypertension, and cardiovascular disorders. This community service activity aimed to provide free health screenings, including blood glucose, cholesterol, and uric acid checks, for elderly residents in RW 03, Utama Subdistrict, South Cimahi District, Cimahi City. Conducted on June 17, 2025, the program involved 52 participants. The results showed that 5.76% had elevated blood glucose, 55.76% had high cholesterol, and 51.92% had excessive uric acid levels. This initiative, supported by local healthcare professionals, intended to raise awareness about the importance of early detection and promote self-care practices. Despite challenges such as limited availability of the implementing team and unpredictable weather, the program was successfully executed. The output of this community service is planned to be published in a nationally accredited journal.